Mixture of Bacillus Amyloliquefaciens and Bacillus Pumilus Modulates Community Structures of Rice Rhizosphere Soil to Suppress Rice Seedling Blight - Jiang Nan; Qiu Jiehua; Tian Dagang; Shi Huanbin; Liu Zhiquan; Wen Hui; Xie Shuwei; Chen Huizhe; Wu Meng; Kou Yanjun (Rice Science)
Rice seedling blight, caused by various fungi, including Fusarium oxysporum, poses a severe threat to rice production. As awareness grows regarding the environmental and safety hazards associated with the application of fungicides for managing rice seedling blight, there has been a shift in focus towards biological control agents. In this study, we isolated biocontrol bacteria from paddy fields that significantly inhibited the growth of F. oxysporum in vitro and identified the strains as Bacillus amyloliquefaciens T40 and Bacillus pumilus T208. Additionally, our findings indicated that the combined application of these Bacillus strains in soil was more effective in reducing the incidence of rice seedling blight than their individual use. Analysis of 16S and internal transcribed spacer rRNA gene sequencing data revealed that the mixture of the T40 and T208 strains exhibited the lowest average clustering coefficients, which were negatively correlated with the biomass of F. oxysporum-inoculated rice seedlings. Furthermore, this mixture led to higher stochastic assembly (average |βNTI| < 2) and reduced selection pressures on rice rhizosphere bacteria compared with individual strain applications. The mixture of the T40 and T208 strains also significantly increased the expression of defense-related genes. In conclusion, the mixture of the T40 and T208 strains effectively modulates microbial community structures, enhances microbial network stability, and boosts the resistance against rice seedling blight. Our study supports the development and utilization of biological resources for crop protection.